An investigation into the recovery of oxide copper from a complex copper ore using sulphidisation technique and hydroxamate and potassium amyl xanthate collectors. Issue 1 (2nd January 2020) - Zare, Ahad; Azizi, Asghar; Karamoozian, Mohammad
ABSTRACT: This study was aimed to increase the floatability of oxide copper from a complex copper sample. For this purpose, sulphidisation processes such as slug and controlled potential sulphidisation (CPS) and hydroxamate and potassium amyl xanthate (Z6) collectors were utilized and their results were compared with real conditions. The results indicated that about 9.46% of the recovery of oxide copper increased using 300g/t ammonium sulphide in the first step, and reached to 77.12%. Also, in this case, the recovery of sulphide copper was significantly improved. In addition, the findings demonstrated that applying 10 g/t of potassium octyl hydroxamate anionic collector, the recovery of oxide copper reached to 74.47% without any negative effect on the recovery of sulphide copper. Meanwhile, the simultaneous use of Z11 and Z6 as collector caused to increase about 3.63% of the recovery of oxide copper (71.29%). It was also found that the highest recovery of oxide copper could be obtained using CPS method and in this case, 10.34% of the oxide copper and 4.48% of the total copper improved and also the dosage of (NH4 )2 S decreased.